Measuring psychological inflexibility in adult and child hearing loss. (3rd October 2019) - Ong, Clarissa W.; Whicker, John J.; Muñoz, Karen; Twohig, Michael P.
Abstract: Objective: Hearing loss is a chronic condition that impacts functioning among individuals with hearing loss and caregivers of children with hearing loss. Even though treatments for hearing loss can alleviate functional impairment, psychological factors like psychological inflexibility may interfere with treatment engagement and adherence, undermining the benefits of treatment. Measuring psychological inflexibility may inform care providers' case conceptualisation, improving the quality and precision of audiological interventions. Thus, this study aimed to develop and validate measures of psychological inflexibility in hearing loss for adults and caregivers of children with hearing loss. Design: Participants were invited to complete an online survey. Study samples: Our sample comprised adults with hearing loss ( N  = 264) and primary caregivers of children with hearing loss ( N  = 275). Results: The final versions of Acceptance and Action Questionnaire-Adult Hearing Loss (AAQ-AHL) and Acceptance and Action Questionnaire-Management of Child Hearing Loss (AAQ-MCHL) showed good to excellent internal reliability and concurrent and discriminant validity. Conclusion: Although the AAQ-AHL and AAQ-MCHL showed acceptable psychometric properties, more tests are needed to further validate these measures and verify their utility in research and clinical settings.